Keefektifan Model Teams Games Tournament Terhadap Minat Belajar - Lutfiyani, Angilia Herli (Universitas Pendidikan Ganesha, 2019)
This study aims to determine the effectiveness of the Teams Games Tournament learning model on the interest in learning in fifth grade students of SDN 01 Ngeling, Jepara Regency. This type of research is a quantitative study with the design of Pre Experimental Design in the form of One-Group Pretest Posttest Design. Data in the study were obtained through (1) observation, (2) questionnaire sheets, and (3) documentation. For data analysis in this study using the normality test and t test (hypothesis test). The results of the analysis of student learning interest questionnaire sheets before and after treatment using the Teams Games Tournament learning model have increased, as seen from the results of the t test that t count> t table is 9,305> 2,110. So the conclusion is the Teams Games Tournament model is effective against students' learning interests